Correlation of Electrical Resistivity and Mackintosh Probe - Abd Malik b Abdullah, Abd Malik (Universiti Teknologi Petronas, 2010)
The objective of this project is to obtain on the possible correlation of electrical resistivity and mackintosh probe. This research however, purposely to implement a simple and quick assessment method to predict the soil properties in the soil investigation in the future.